Pengaruh Investment Opportunity Set, Return on Asset dan Kepemilikan, Manajerial terhadap Kebijakan Dividen dengan Likuiditas sebagai, Variabel Moderasi: : Studi kasus pada Perusahaan Manufaktur yang, terdaftar di Bursa Efek Indonesia Tahun 2017-2021 - Nanda Putri Mawarda; Desi Ika; Liza Novietta (Masyarakat Ekonomi Syariah Bogor, 2024)
This study aims to determine the influence of Investment, Opportunity Set, Return On Asset and Ownership Managerial against Policy, Dividend, with Liquidity as Variable Moderation on manufacturing companies listed on the Indonesia Stock Exchange in 2017-2021. The population in this study is manufacturing companies listed on the Indonesia Stock Exchange in 2017-2021. This research is a type of associative research. The number of samples in this study amounted to 36 companies from 216 populations during the 5th consecutive year of observations so the total sample was 180 observational data. The analysis technique used is Moderated Regression Analysis (MRA). In this case researchers used residual testing methods. Data collection techniques are using literature studies and documentation through the official website of the Indonesia Stock Exchange, namely www.idx.co.id. The results showed that Investment Opportunit Set (IOS) had a positive but not significant effect on Dividend Policy (DPR), Return On Assets (ROA) had a negative and insignificant effect on Dividend Policy (DPR), Managerial Ownership (KM) had a negative and insignificant effect on Dividend Policy (DPR), Liquidity (CR) had a negative and insignificant effect on Dividend Policy (DPR), Liquidity (CR) cannot moderate the effect of Investment Opportunity Set (IOS) on Dividend Policy (DPR), Liquidity (CR) cannot moderate the effect of Return On Asset (ROA) on Dividend Policy (DPR), Liquidity (CR) cannot moderate the effect of Managerial Ownership (KM) on Dividend Policy (DPR) in Manufacturing Companies Listed on the Indonesia Stock Exchange for the 2017-2021 Period.